CREATING HARMONY AND SUSTAINABILITY THROUGH RAMPAK NAONG BRINGEN KORONG - BASED MANAGEMENT CONTROL SYSTEM - Bonnie Soeherman; Sharon Leonata Itam (Universitas PGRI Madiun, 2022)
ABSTRACTThis research aims to empirically see how leaders' role in creating tone as a form of culture-based Management Control System. This study uses a qualitative interpretive approach to obtain a holistic picture of a unique phenomenon, the story of the tobacco trading business in Bondowoso, which Madurese workers dominate. Business practice is thick with the value of